A review of engagement strategies for massive open online courses - Md Nujid, Masyitah binti; Tholibon, Duratul Ain (Institute of Advanced Engineering and Science, 2024)
The United Nations adopted the sustainable development goal of “quality education” as one of its objectives. In emergency teaching and learning amid the outbreak in 2019, the emphasis has been placed on providing a versatile and easily accessible lifelong learning experience to ensure high-quality education. One type of online e-learning course is the massive open online course (MOOC). It provides a free course that may be taken whenever and anywhere. However, difficulties have come up regarding student performance, course completion, and dropping out as a result of quality assurance of e-learning platforms like MOOC. In order to keep students interested in the course until the end, this study will review and recommend MOOC strategies. The strategies in enhancing for MOOC engagement reveals that they include development, collaboration between educators and students, and evaluation. Self-regulation learning is a crucial motivation in retention from dropping out of the MOOC facilitates participation through the utilization of innovative pedagogies, as well as the interaction between students and educators on both the MOOC platforms and social media platforms according to research. Course information and instructional design are also found to attract learners to complete the course. Giving prizes for completing MOOC assignments and tests is an extra choice in retaining from dropping out the course. The contribution of study is MOOC online learning engagement strategies are introduced. By developing a good course design, collaboration between students and educators and evaluation performance based can enhance students’ engagement to completion of the course.